Cost-effectiveness analysis of exenatide once-weekly versus dulaglutide, liraglutide, and lixisenatide for the treatment of type 2 diabetes mellitus: an analysis from the UK NHS perspective. (1st December 2016) - Chuang, L. H.; Verheggen, B. G.; Charokopou, M.; Gibson, D.; Grandy, S.; Kartman, B.
Abstract: Objective: To assess the cost-effectiveness of exenatide 2 mg once-weekly (EQW) compared to dulaglutide 1.5 mg QW, liraglutide 1.2 mg and 1.8 mg once-daily (QD), and lixisenatide 20 μg QD for the treatment of adult patients with type 2 diabetes mellitus (T2DM) not adequately controlled on metformin. Methods: The Cardiff Diabetes Model was applied to evaluate cost-effectiveness, with treatment effects sourced from a network meta-analysis. Quality-adjusted life years (QALYs) were calculated with health-state utilities applied to T2DM-related complications, weight changes, hypoglycemia, and nausea. Costs (GBP £) included drug treatment, T2DM-related complications, severe hypoglycemia, nausea, and treatment discontinuation due to adverse events. A 40-year time horizon was used. Results: In all base-case comparisons, EQW was associated with a QALY gain per patient; 0.046 vs dulaglutide 1.5 mg; 0.102 vs liraglutide 1.2 mg; 0.043 vs liraglutide 1.8 mg; and 0.074 vs lixisenatide 20 μg. Cost per patient was lower for EQW than for liraglutide 1.8 mg (−£2, 085); therefore, EQW dominated liraglutide 1.8 mg. The cost difference per patient between EQW and dulaglutide 1.5 mg, EQW and liraglutide 1.2 mg, and EQW and lixisenatide 20 μg was £27, £103, and £738, respectively. Cost per QALY gained with EQW vs dulaglutide 1.5 mg, EQW vs liraglutide 1.2 mg, and EQW vs lixisenatide 20 μg was £596, £1, 004, and £10, 002, respectively. In the probabilistic sensitivity analysis, the probability that EQW is cost-effective ranged from 76–99%. Conclusion: Results suggest that exenatide 2 mg once-weekly is cost-effective over a lifetime horizon compared to dulaglutide 1.5 mg QW, liraglutide 1.2 mg QD, liraglutide 1.8 mg QD, and lixisenatide 20 μg QD for the treatment of T2DM in adults not adequately controlled on metformin alone.